Análisis del impacto de la ley orgánica para la promoción del trabajo juvenil, regulación excepcional de la jornada de trabajo, cesantía y seguro de desempleo, sobre el desempleo juvenil en ecuador. - Dávila Cueva, Dayana del Cisne (2022)
Youth unemployment is one of the main problems facing the globalized world. In the case of Ecuador, according to the National Institute of Statistics and Censuses (INEC) (2020), until December 2019, 37.6% of the unemployed population was made up of people between 15 and 24 years old. In this sense, this research focuses on evaluating the impact on youth unemployment of the Organic Law for the Promotion of Youth Work, Exceptional Regulation of the Working Hours, Unemployment and Unemployment Insurance (LOTJ) approved in 2016, through a descriptive and econometric analysis during 2007-2020. Control variables are included referring to the social, economic, demographic and cultural conditions faced by young people between 18 and 26 years of age. The data was extracted from the National Survey on Employment, Unemployment and Underemployment (ENEMDU) published by the INEC (2021) and includes information from 21 provinces of Ecuador. The Propensity Score Matching (PSM) method was used, with which it was obtained that, effectively, the implementation of the LOTJ significantly reduced youth unemployment in the period after its creation. In addition, it was found that the labor context in the provinces is heterogeneous and depends largely on its productive structure. Given this scenario, it is suggested that the State implement public policies based on regulatory mechanisms to insert young people into the labor market, for example, through legal incentives that prioritize the hiring of young people in private companies.